Evaluation of the cytotoxic activity and toxicity of a tropolone derivative with a potential antitumor effect - O. I. Kit; V. I. Minkin; E. A. Lukbanova; Yu. A. Sayapin; E. A. Gusakov; A. O. Sitkovskaya; S. Yu. Filippova; E. F. Komarova; A. V. Volkova; D. V. Khodakova; M. V. Mindar; Yu. N. Lazutin; et al. (Бюллетень сибирской медицины)
The aim. To study the toxicity of 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone in vitro and in vivo.Materials and methods. 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone was synthesized using a method for expanding the o-quinone cycle during the reaction between 5-nitro-2,6,8-trimethyl4-chloroquinoline and 3,4,5,6-tetrachloro-1,2-benzoquinone while boiled in dioxane. An in vitro experiment was carried out in the human A549 cell line. Cell viability was assessed using the MTT colorimetric assay by reducing the optical density of the experimental samples compared with the control ones. Acute toxicity was studied on 20 BALB/c Nude male mice. The test compound was administered once orally as a suspension in 1% starch gel at three doses: 0.0055 (group 1), 0.055 (group 2) and 0.55 mg / g (group 3). The control group (group 4) received a placebo.Results. We synthesized a new compound, 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone. Its structure was established by 1 H nuclear magnetic resonance (NMR), infrared (IR) spectroscopy, and mass spectrometry. The yield was 19.8 g (52%), the melting point was 205–207 ºС, bright yellow crystals (benzene) were observed. The half-maximal inhibitory concentration (IC50) of 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone was 0.21 ± 0.01 μM, which was significantly lower (р < 0.05) than the IC50 of cisplatin (3.84 ± 0.23). Following the in vivo experiment, no toxic effect of tropolone was detected when administered once at a dose of 0.0055, 0.055, and 0.55 mg / g. Conclusion. 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone demonstrated cytotoxic effects on the A549 cell line at a lower IC50 than cisplatin which is widely used in treatment of cancers, including lung cancer. Insolubility of 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone in water and the absence of its toxic effect in the studied modes determine the scope of its application for further study of cumulative and antitumor effects.